Identifying the tooth shade in group of patients using Vita Easyshade - Elamin, Habab Osman; Abubakr, Neamat Hassan; Ibrahim, Yahia Eltayib (European Journal of Dentistry, 2015)
Objective: The aim of the present investigation is to identify tooth shade among a group of Sudanese patients. Materials and Methods: Total number of patients was 227. Participant's age ranged from 15 to 72 years, which, was divided into four groups. The tooth included in the study was either right or left sounds maxillary central incisor. Vita Easyshade was used to select the tooth shade. Investigation of the differences of Commission International de l'Eclairage (CIELab) coordinates among gender and state of origin was conducted together with an examination of the relationship between CIELab coordinates and age. One-way analysis of variance was used to test the differences in L*, a* and b* according to state of origin. Results: Results showed that A3 was the most common classical tooth shade respectively. There was highly significant difference in L* between males and females (P = 0.002). There was a significant relation between tooth shade and age (P = 0.026). There was a high significant association between classical tooth shade and Sudan regions (P = 0.00). Conclusion: In conclusion, most common classical shade was A3, women's teeth were lighter than men's. There was a relation between ethnic background and tooth shade.
Keywords: Esthetics; Commission International de l'Eclairage; tooth shade; Vita Easyshade